Design of a voltammetry system for in vivo measurement of dopamine concentration - Riaz, Raheel (İstanbul Medipol Üniversitesi Fen Bilimleri Enstitüsü, 2018)
Dopamine has a critical role in motor control, motor learning, reinforcement learning, cognition, attention and motivation. Consequently, the physiology of the dopaminergic system is an important and highly active research topic. Fast-scan cyclic voltammetry (FSCV) technique enables in vivo measurement of dopamine concentration with high, subsecond temporal resolution. In this study, our aim was to propose a low-cost and practical FSCV system that enables the recording of the phasic changes in dopamine concentration in the rat brain during behavioral experiments. We developed the voltammetry hardware using a microcontroller and a combination of analog integrated circuits (ICs) to generate a triangular voltametric waveforms phase-locked to mains frequency and to apply these waveforms to a carbon ?ber microsensor. The voltammetric current through the microsensor is converted to voltage, ampli?ed, ?ltered using the hardware and then fed to a data acquisition card on a PC. A LabVIEW application is also developed to control the data acquisition hardware, digital ?ltering of the recorded signals and storage of the data. In order to validate the practicality of the system, we chronically implanted one rat with carbon ?ber microsensor in the ventromedial striatum (VMS) and recorded the voltammetric signals 1) in response to presentation of unexpected primary rewards (unconditioned stimuli), 2) in response to presentation of reward predictive stimuli (cue light) and 3) during electrical stimulation of dopaminergic pathway. Based on 5 recording sessions in which unexpected rewards were presented and 5 recording sessions in which predictive stimuli were presented, the phasic increase in the dopamine concentration was measured as 50.5±13.1 nM and 40.2±13.9 nM, respectively. The peak increase in dopamine concentration with electrical stimulation of the dopaminergic pathway during implantation surgery was measured as 132.8 nM. Our results based on the recordings from one rat indicate that phasic increases in dopamine concentration in the VMS in response to delivery of unexpected rewards and reward predictive stimuli can be detected using the proposed system. The cost of the present FSCV system is approximately $1200.

Dopamin motor control, motor öğrenme, pekiştirmeli öğrenme, bilişsellikte, dikkat ve motivasyonda kritik öneme sahiptir. Bu yüzden dopaminerjik sistem ?zyolojisi önemli ve aktif bir araştırma konusudur. Hızlı tarama döngüsel voltametri (HTDV) tekniği yüksek, saniye alt zamansal çözünürlu¨kle in vivo dopamin konsantrasyonu ölçümlerini mümkün hale getirmektedir. Bu çalışmadaki amacımız davranış deneyleri sırasında sıçan beyninde dopamin konsantrasyonu değişimlerinin kaydedilmesini mümkün hale getiren düşük maliyetli ve uygulanabilir bir HTDV sistemi geliştirmektir. Şebeke frekansı fazna kilitlenmi gen ekilli dalgalar retmek ve bu dalgalar mikroalgılayıcıya uygulayabilmek için voltametri donanımı bir mikrodenetleyici ve analog entegre devrelerin bir kombinasyonunu kullanarak geliştirdik. Mikroalgıyıcı aracılığıyla alınan voltametrik akım bu donanımla voltaja çevrilmekte, kuvvetlendirilmekte, ?ltrelenmekte ve ardından PC üzerindeki bir veri toplama kartına iletilmektedir. Veri toplama kartını kontrol etmek, sayısal ?ltreleme yapmak ve veri kaydı için de bir LabVIEW uygulaması geliştirdik. Sistemin uygulanabilirliğini doğrulamak için sıçan ventromedial striatumuna (VMS) kronik olarak karbon ?ber mikroalgılayıcılar implante ettik ve 1) sIıçana beklenmedik anlarda ödüller verildiği, 2) ödülün kestirimcisi uyaranlar verildiği ve 3) dopaminerjik yolakların elektriksel olarak uyarıldığı sırada voltametrik işretleri kaydettik. Beklenmedik ödüllerin verildiği 5 deneme ve ödül kestirimcisi uyaranlarn verildiği 5 deneme sırasında alınan kayıtlara göre dopamin konsantrasyonundaki fazik artış sırasıyla 50.5±13.1 nM and 40.2±13.9 nM olarak ölçüldü. Dopaminerjik yolakların implantasyon ameliyatı sırasında elektriksel olarak uyarıldığında en yüksek dopamin konsantrasyonu artışı 132.8 nM olarak ölçüldü. Bir sıçandan aldığımız kayıtlar önerdiğimiz sistemi kullanarak ventromedial striatumdaki fazik dopamin konsantrasyonu artışlarının beklenmedik ödüller ve ödülün kestirimcisi uyaranlar verildiğinde tespit edilebileceğini göstermiştir. Önerdiğimiz HTDV sistemin maliyeti yaklaşık olarak 1200 USD'dir.
İn vivo dopamin konsantrasyonu ölçümüiçin voltametri sistemi tasarımı
Keywords: Dopamine; Voltammetry; FSCV; VMS; LabVIEW; Dopamin; Voltameri; HTDV; LabVIEW; VMS